PENGARUH PENERAPAN MEDIA PEMBELAJARAN SMARTBOARD TERHADAP KEMAMPUAN BERNALAR KRITIS SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SD NEGERI 2 SAGARAHIANG - Mela Krisdayanti; Agatha Kristi Pramudika Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to determine the effect of implementing Smartboard learning media on the critical reasoning abilities of class IV students at SD Negeri 2 Sagarahiang. The method in this research is Quantitative Quasi Experiment Design with a Nonequivalent Control Group Design. The population and sample were all fourth grade students at SD Negeri 1 and SD Negeri 2 Sagarahiang, totaling 47 students. The instruments in this research used observations of learning implementation on teachers and students as well as critical reasoning ability tests in the form of a Pre-test and Post-test with a total of 10 questions. Based on the results of research and data analysis, the results showed that: (1) the implementation of observations on teachers and students was carried out very well. (2) learning using Smartboard media influences students' critical reasoning abilities. This result is proven by obtaining the Sig hypothesis results. (2-tailed) = 0.002 < 0.005 then H1 is accepted. It can be concluded that the application of Smartboard learning media has an effect on the critical reasoning abilities of class IV students at SD Negeri 2 Sagarahiang.